2013
DOI: 10.1111/eos.12057
|View full text |Cite
|
Sign up to set email alerts
|

Various irrigation protocols for final rinse to improve bond strengths of fiber posts inside the root canal

Abstract: Irrigation after post space preparation and its effects on the bond strength of different adhesive strategies are still an issue of interest. The aim of the present study was to investigate the effects of various irrigation protocols (IPs) on the push-out bond strengths of fiber posts. One-hundred and fifty extracted human anterior teeth were divided into three groups (n = 50 each) and endodontically treated. The post space was irrigated before post placement using the following five IPs in each group: IP1 (co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 29 publications
3
49
0
10
Order By: Relevance
“…In general, specimens that had the dentin surface treated with NaOCl alone presented the lowest BS. These findings are consistent with those of other studies, 36,37 which revealed that pre-treatment of dentin with EDTA increased the BS of self-etch adhesive systems. In fact, NaOCl alone does not remove the smear layer, 38 maintaining the dentinal tubules closed and impeding penetration of the luting cement, and so the combination of NaOCl and EDTA is the main indication to remove remaining organic and inorganic matter.…”
Section: A B C D E Fsupporting
confidence: 93%
See 2 more Smart Citations
“…In general, specimens that had the dentin surface treated with NaOCl alone presented the lowest BS. These findings are consistent with those of other studies, 36,37 which revealed that pre-treatment of dentin with EDTA increased the BS of self-etch adhesive systems. In fact, NaOCl alone does not remove the smear layer, 38 maintaining the dentinal tubules closed and impeding penetration of the luting cement, and so the combination of NaOCl and EDTA is the main indication to remove remaining organic and inorganic matter.…”
Section: A B C D E Fsupporting
confidence: 93%
“…26 These differences could be attributed to particular features of the dentin substrate or even to the incomplete removal of demineralized collagen zone due to low concentration of the solution and or insufficient application time. 36 In the present study, EDTA was applied for 20s, based on Calt & Serper, 40 who showed that the application of the chelating agent over 1 min promotes erosion of peritubular dentin. A 2.5% NaOCl solution was applied for 1 min and probably this concentration was not sufficient to remove the demineralized collagen zone.…”
Section: A B C D E Fmentioning
confidence: 88%
See 1 more Smart Citation
“…The characteristics of the 9 included studies are summarized in Table 1. 8,17,19,23,24,25,26,27,28 Eleven studies that did not meet the inclusion criteria ( Figure 1) To investigate the effect of QMix irrigant compared with several other irrigating solutions on the bond strength of glass fibre posts to root dentine and on smear layer removal after post space preparation.…”
Section: Resultsmentioning
confidence: 99%
“…15 Moreover, activation methods of irrigation solutions have been used as an additional method to increase their effectiveness, such as the use of ultrasonic systems and laser devices. 16,17,18 Despite the large number of in vitro studies in the literature, there is currently no consensus on the best solution for removing debris after post-space preparation, while it remains unclearif this can affect the bond strength of FGPs to root dentin. 19 Therefore, the objective of this study was to systematically review the literature using in vitro studies to investigate if cleaning methods of root canal after post-space preparation can increase the retention of FGPs evaluated by push-out test.…”
Section: Introductionmentioning
confidence: 99%